Papel do tecido adiposo perivascular em aorta de ratos treinados e alimentados com dieta hiperlipídica - Araujo, Hygor Nunes [UNESP] (2015)
The importance of perivascular adipose tissue (PVAT) in vascular function has recently been recognized. The aim of this study was to evaluate the effects of perivascular adipose tissue in the aorta responsiveness from trained rats fed with high fat diet. Male Wistar (290-320 g) rats were divided into: Control sedentary (c-SD), High fat diet sedentary (dh-SD), Trained (c-TR) and High fat diet trained (dh-TR). For sixteen weeks c-SD and c-TR groups were fed with standard chow and dh-SD and dh-TR groups were fed with high fat diet. After eight weeks, c-TR and dh-TR groups initiated the aerobic exercise training on treadmill, 5 days/week, 60 min/session (10 min at 40% of maximum speed, 40 min at 50-60% of maximum speed, and 10 min at 40% of maximum speed) and 0% grade until the end of the protocol. Concentration-response curves to acetylcholine (ACh), sodium nitroprusside (SNP), phenylephrine (PHE) and serotonin (5-HT) were obtained in thoracic aorta without (PVAT-) or with (PVAT +) the PVAT. The concentrations of glucose, total cholesterol (CT), triglycerides (TG), insulin and leptin were evaluated. The protein expressions of endotelial nitric oxide synthase (eNOS) in aorta and inducible nitric oxide synthase (iNOS) in PVAT were determined. The high fat diet increased the body weight gain, epididymal fat pad, TG, insulin and leptin in dh-SD group compared to c-SD, whereas TR reduced these values in dh-TR group. Relaxing response: The PVAT+ rings did not modify the potency (pEC50) and the maximal response (EMAX) to ACh and SNP agents. Contractile responses: The PVAT reduced the EMAX to PHE (mN/mm) in all groups: c-SD (PVAT+: 3.5±0.4 and PVAT-: 6.8±0.5), c-TR (PVAT+: 4.7±0.8 and PVAT-: 7.9±1.4), dh-SD (PVAT+: 2.1±0.2 and PVAT-: 6.1±0.6) and dh-TR (PVAT+: 2.5±0.4 and PVAT-: 5.8±0.5), in a similar magnitude. We also found an anticontractile effect to 5-HT: c-SD (PVAT+: 7.0±0.9 and PVAT-: 9.7±1.3), c-TR ...